2017
DOI: 10.3831/kpi.2017.20.008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of an Ethanol Extract of Cassia Abbreviata Stem Bark on Diabetic Rats and Possible Mechanism of Its Action

Abstract: Objectives:This study aimed to evaluate the hypoglycemic effects of an ethanol extract of Cassia abbreviata (ECA) bark and the possible mechanisms of its action in diabetic albino rats.Methods:ECA was prepared by soaking the powdered plant material in 70% ethanol. It was filtered and made solvent-free by evaporation on a rotary evaporator. Type 2 diabetes was induced in albino rats by injecting 35 mg/kg body weight (bw) of streptozotocin after having fed the rats a high-fat diet for 2 weeks. Diabetic rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Similar glucose absorption patterns were demonstrated by a study conducted by Seabi et al (2016) on the extracts of C. abbreviata bark, which revealed a dose-dependent glucose uptake by C2C12 cells, with increase by up to 23% and 31% of glucose absorption at 50 mg/ ml and 100 mg/ml, respectively after 3 hour incubation. 14 Furthermore, a recent study by Bati et al (2017) confirmed the anti-diabetic effects of C. abbreviata ethanolic bark extract on diabetic rats. 35 Moreover, Shalaby et al (2014) indicated that the administration of cinnamomum cassia extract in alloxan induced obese diabetic Sprague Dawley rats induced a significant reduction in blood glucose level.…”
Section: Six Hour Glucose Uptakementioning
confidence: 88%
“…Similar glucose absorption patterns were demonstrated by a study conducted by Seabi et al (2016) on the extracts of C. abbreviata bark, which revealed a dose-dependent glucose uptake by C2C12 cells, with increase by up to 23% and 31% of glucose absorption at 50 mg/ ml and 100 mg/ml, respectively after 3 hour incubation. 14 Furthermore, a recent study by Bati et al (2017) confirmed the anti-diabetic effects of C. abbreviata ethanolic bark extract on diabetic rats. 35 Moreover, Shalaby et al (2014) indicated that the administration of cinnamomum cassia extract in alloxan induced obese diabetic Sprague Dawley rats induced a significant reduction in blood glucose level.…”
Section: Six Hour Glucose Uptakementioning
confidence: 88%
“…The other 3 groups were fed an HFD to induce diabetes. After 4 weeks of feeding, all the animals were fasted for 12 h, and then the rats in the diabetes group were intraperitoneally injected with STZ (35 mg/kg body weight), while the rats in the control group were injected with the same volume of citrate buffer (34)(35)(36). The blood glucose levels were measured 72 h after STZ injection.…”
Section: Methodsmentioning
confidence: 99%
“…Cassia abbreviata, is a plant belonging to the Caesalpiniaceae family and is widely distributed across Africa [52]. The roots, stem bark and fruit pulp of C. abbreviata extracts are traditionally used for treatment of inflammatory, fever, joint pains, malaria, diarrhea, leprosy, bilharzias, stomach pains, diabetes mellitus and its complications and other illnesses [53].…”
Section: Cassia Abbreviata (Oliv)mentioning
confidence: 99%